Huaier Cream Protects against Adriamycin-Induced Nephropathy by Restoring Mitochondrial Function via PGC-1α Upregulation - Ruochen Che; Chunhua Zhu; Guixia Ding; Min Zhao; Mi Bai; Zhanjun Jia; Aihua Zhang; Songming Huang (PPAR Research)
The mechanism by which Huaier, a Chinese traditional medicine, protects podocytes remains unclear. We designed the present study to examine whether mitochondrial function restored by PGC-1α serves as the major target of Huaier cream in protecting ADR nephropathy. After ADR administration, the podocytes exhibited remarkable cell injury and mitochondrial dysfunction. Additionally, ADR also reduced PGC-1α both in vivo and in vitro. Following the Huaier treatment, the notable downregulation of PGC-1α and its downstream molecule mitochondrial transcription factor A (TFAM) were almost entirely blocked. Correspondingly, Huaier markedly ameliorated ADR-induced podocyte injury and mitochondrial dysfunction in both rat kidneys and incubated cells as it inhibited the decrease of nephrin and podocin expression, mtDNA copy number, MMP, and ATP content. Transmission electron microscopy result also showed that Huaier protected mitochondria against ADR-induced severe mitophagy and abnormal changes of ultrastructural morphology. In conclusion, Huaier can protect podocytes against ADR-induced cytotoxicity possibly by reversing the dysfunction of mitochondria via PGC-1α overexpression, which may be a novel therapeutic drug target in glomerular diseases.